Determination of association between different Risk Factors & Cardiac Anomalies with Stroke among Adults - Saira John, Nickson Subeston Anthony, Parveen Siddique (Pakistan Journal of Medical & Health Sciences, 2022)
Background: There is presence of different risk factors for cerebrovascular complication as well as coronary artery. It is well acknowledged that diseases of the coronary artery enhance the stroke risk. In opposition to this, there is variation in the prevalence of these risk factors across ischemic stroke and disease of coronary artery as well as between the sub-types of stoke because of highly complicate etiology. Objective: The objective of this research work was to determine different risk factors and cardiac anomalies, which have association with the incidence of stroke among adults. Methodology: Study Design: This cross sectional study design. Place and Duration: Medicine Department of Services Hospital, Lahore from November 2020 to May 2022. Adult patients having age from fifteen to forty-five years of age who got admission in hospital due to occurrence of stroke were the samples of this research work. Results: Among the participants, most of the patients were in age group of 41-45 years making 36 percent of whole strength. The percentages of the patients in age groups 26-30, 31-35 and 36-40 years were 18%, 20% and 22% correspondingly. Only four percent patients were having less than twenty-five years of age. Sixty-four percent patients were suffering from VHD (Valvular Heart Disease). Myocardial infarction was present in sixteen percent patients. Eight percent patients were present with atrial fibrillation and ten percent patients were present with IHD (ischemic heart disease). The risk equation of Framingham heart study discovered that seventy five percent patients of stroke were also having some types of cardiac complications. Conclusion: Diseases of hearts among adults can result in stroke that is severe abnormality and requires to be handled meticulously. One leading cause of disability and mortality is stroke. Ischemic strokes among adults are likely to be related with heart than cerebral when there is unknown exact cause of complication. Keywords: Ischemic, complication, meticulously, determine, occurrence, VHD, ISHD, cardiac, risk factors.